Rangeland Data Gaps - Flintan, Fiona E. (International Livestock Research Institute, 2024)
A presentation on why we need a global rangelands data platform, made at the GEF-funded STELARR project meeting 24-24 October, 2023 on a global rangelands data platform, developed by ILRI and partners.